Organ Growth and Intestinal Functions of Preterm Pigs Fed Low and High Protein Formulas With or Without Supplemental Leucine or Hydroxymethylbutyrate as Growth Promoters - Buddington, Randal K.; Yakimkova, Taisiya; Adebiyi, Adebowale; Chizhikov, Victor V.; Iskusnykh, Igor Y.; Buddington, Karyl K. (Frontiers in Nutrition, 2021)
The goal of enteral nutritional support for infants born preterm or small for gestational age (SGA) is to achieve normal growth and development. Yet, this is difficult to achieve because of intestinal immaturity. Our objective was to determine if birth weight, protein intake, and the growth promoters leucine (10 g/L) or calcium-ß-hydroxy-ß-methylbutryate (HMB; 1.1 g/L) would affect trajectories of intestinal growth and functions and weights of other organs. Preterm pigs were delivered at gestational day 105 (91% of term) and fed for 6 or 7 days isocaloric formulas that differed in protein content (50 g or 100 g protein/L), with and without the growth promoters leucine or HMB. For comparative purposes organ weights were measured within 12 h after delivery for six term pigs of low and six of average birth weights. The responses of intestinal growth and total intestinal brush border membrane carbohydrases to protein level and supplemental leucine were of greater magnitude for preterm pigs of lower birth weight. Forskolin stimulated chloride secretion in the proximal small intestine was lower for pigs fed the low protein milk replacers. Capacities of the entire small intestine to transport glucose (mmol/kg-day) were not responsive to protein level, leucine, or HMB, and did not differ between small and large pigs. Relative organ weights of the small and average weight term pigs were similar, but some differed from those of the preterm pigs suggesting preterm birth and the standards of care used for this study altered the trajectories of development for the intestine and other organs. Although leucine is an effective generalized growth promoter that enhances gut development of small preterm pigs, it does not mitigate compromised neurodevelopment. Our findings using preterm pigs as a relevant preclinical model indicate nutrition support strategies can influence development of some gastrointestinal tract characteristics and the growth of other organs.